Fostering Environmental Literacy through the Curriculum at School Level: NEP 2020's Approach and its Implications - Anshul Saluja (Utan Kayu Publishing, 2024)
Environmental literacy is essential for individuals to comprehend, appreciate, and appropriately solve the urgent environmental issues affecting our globe. In India, the National Education Policy (NEP) 2020 acknowledges the value of instilling environmental consciousness and sustainability in students at a young age. This study examines how NEP 2020 anticipates the inclusion of environmental literacy in the overall school curriculum and considers any potential effects on students, teachers, and the community at large. This article intends to identify the policy's goals, tactics, and expected effects on students' environmental consciousness by scrutinising the clauses and suggestions in NEP 2020 that pertain to environmental education at the school level. The article further explores the application of curricular adaptation, instructional strategies, and evaluation tools intended to advance environmental literacy. By closely examining the provisions and recommendations in NEP 2020 that relate to environmental education at the school level, this paper seeks to establish the policy's objectives, strategies, and anticipated consequences on students' environmental consciousness. The article investigates the use of curriculum modification, teaching techniques, and assessment instruments designed to enhance environmental literacy. The preliminary findings suggest that NEP 2020's approach to fostering environmental literacy through the curriculum has the potential to create environmentally conscious citizens who recognize the interdependence between humans and the environment. Further observations suggest that the alignment of this approach with global trends in education emphasizes sustainability, citizenship, and the need for a comprehensive understanding of environmental issues.